Early weight regain after gastric bypass does not affect insulin sensitivity but is associated with elevated ghrelin. (29th April 2014) - Tamboli, Robyn A.; Breitman, Igal; Marks‐Shulman, Pam A.; Jabbour, Kareem; Melvin, Willie; Williams, Brandon; Clements, Ronald H.; Feurer, Irene D.; Abumrad, Naji N.
<x xml:space="preserve">Abstract</x> Objectives We sought to determine: (1) if early weight regain between 1 and 2 years after Roux‐en‐Y gastric bypass (RYGB) is associated with worsened hepatic and peripheral insulin sensitivity, and (2) if preoperative levels of ghrelin and leptin are associated with early weight regain after RYGB. Methods Hepatic and peripheral insulin sensitivity and ghrelin and leptin plasma levels were assessed longitudinally in 45 subjects before RYGB and at 1 month, 6 months, 1 year, and 2 years postoperatively. Weight regain was defined as ≥5% increase in body weight between 1 and 2 years after RYGB. Results Weight regain occurred in 33% of subjects, with an average increase in body weight of 10 ± 5% (8.5 ± 3.3 kg). Weight regain was not associated with worsening of peripheral or hepatic insulin sensitivity. Subjects with weight regain after RYGB had higher preoperative and postoperative levels of ghrelin compared to those who maintained or lost weight during this time. Conversely, the trajectories of leptin levels corresponded with the trajectories of fat mass in both groups. Conclusions Early weight regain after RYGB is not associated with a reversal of improvements in insulin sensitivity. Higher preoperative ghrelin levels might identify patients that are more susceptible to weight regain after RYGB.